(3QSGdI aj JMQje GdONGfs - (3CMeO Hf eMeO GdHdHjSj GdGRgQjs
(3ChdgG (B:s
(3GdMeO ddg GdPi LHd bdH ef GUWaGg ef YHGOg s
(3BNQgG (B:s
(3hGdMeO ddg QH GdYGdejf ChdkG hBNQkG , hHGWfkG hXGgQkG dGFbkG Hc efc jG QH GdYGdejf JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdNGeS hGdYTQhfs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdCSJGP GdOcJhQ GSMGb ehSi GdMSjfi GdNGUI s
Keywords: (3Gdabg GdTGaYjs